2004
DOI: 10.1249/01.mss.0000139802.96395.ac
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Power Prediction Equations: Peak Vertical Jumping Power in Women

Abstract: colon; Changes in peak power is accurate using any of the regression equations; however, the new prediction formula and that of Harman seem to more precisely estimate peak power. Strict jumping technique along with simultaneous measurement of power and jump height should be used as the standard for comparison.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
0
13

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(112 citation statements)
references
References 11 publications
5
90
0
13
Order By: Relevance
“…Subjects were randomly assigned to a plyometric training intervention group or a control group and performed maximal countermovement vertical jumps on a force platform both before and after the six-week intervention period. Canavan and Vescovi (2004) found that the Sayers equation overestimated peak power, but suggested that this overestimation could be due to the different methods of quantifying vertical jump height (i.e., jump-and-reach method to collect vertical jump height data by Sayers et al (1999) vs. use of a force platform to calculate jump height data in the current analysis by Canavan and Vescovi (2004)). The authors concluded that the predictive model developed in their investigation appeared to be highly accurate and provided a more precise estimate of peak power compared to the Sayers et al (1999) and Harman et al…”
Section: Rationale For Choosing the Sayers Equation As The Predictivementioning
confidence: 92%
See 2 more Smart Citations
“…Subjects were randomly assigned to a plyometric training intervention group or a control group and performed maximal countermovement vertical jumps on a force platform both before and after the six-week intervention period. Canavan and Vescovi (2004) found that the Sayers equation overestimated peak power, but suggested that this overestimation could be due to the different methods of quantifying vertical jump height (i.e., jump-and-reach method to collect vertical jump height data by Sayers et al (1999) vs. use of a force platform to calculate jump height data in the current analysis by Canavan and Vescovi (2004)). The authors concluded that the predictive model developed in their investigation appeared to be highly accurate and provided a more precise estimate of peak power compared to the Sayers et al (1999) and Harman et al…”
Section: Rationale For Choosing the Sayers Equation As The Predictivementioning
confidence: 92%
“…A longitudinal study by Canavan and Vescovi (2004) compared the actual peak power assessed using a force platform and the estimated peak power values derived using the Sayers et al and Harman et al equations. As rationale for comparing these equations, the authors identified the heterogeneous subject population used by Sayers et al (1999), comprised of both athletes and non-athletes of both sexes, as a limitation that necessitated examination of the resulting prediction equation.…”
Section: Rationale For Choosing the Sayers Equation As The Predictivementioning
confidence: 99%
See 1 more Smart Citation
“…One minute after the warm up, players performed three countermovement jumps conducted on a piezoelectric force platform (KMS, Australia). During the assessment, all the athletes placed both hands on their hips to avoid any upper body influence on the result [19]. A two minute rest period was allowed between each jump to ensure maximal effort [20].…”
Section: Maximal Vertical Jumpmentioning
confidence: 99%
“…Figure 1 illustrates the Ollie maneuver. It allows the skater to pass over, mount or slide along obstacles and requires considerable skill and timing (BRIDGMAN;COLLINS;COLLINS, 1992) and most other maneuvers are combinations of the Ollie with turns of the skateboard and the athlete's body (CANAVAN;VESCOVI, 2004). Given that the Ollie maneuver is involved in most skateboarding movements it is important to study it in order to improve the performance of the athletes.…”
Section: Introductionmentioning
confidence: 99%